Simultaneous Bilateral Proximal Humerus Fractures Treated with Single-Stage Bilateral Reverse Shoulder Arthroplasty - Taiki Tokuhiro; Atsushi Urita; Yusuke Kameda; Makoto Motomiya; Naoya Watanabe; Norimasa Iwasaki (Case Reports in Orthopedics)
Introduction. Simultaneous bilateral fractures of the proximal humerus are infrequent, and simultaneous bilateral three- or four-part fractures are even rarer. Reverse shoulder arthroplasty (RSA) is being used increasingly for the treatment of three- and four-part fractures of the proximal humerus. However, treatment of simultaneous bilateral fractures of the proximal humerus is difficult because of concern about postoperative immobilization and rehabilitation. Case Presentation. A 75-year-old woman presented with bilateral shoulder pain subsequent to a fall on the street. Physical examination and radiographs showed simultaneous bilateral fractures of the proximal humerus. The right side fracture was classified as a four-part fracture and the left side fracture as a three-part fracture, according to Neer’s classification. The right shoulder had a risk of avascular necrosis of the humeral head. For the left shoulder, the fracture type had caused ischemia of the humeral head. Single-stage bilateral RSA was performed 9 days after the injury. An abduction pillow was applied for 5 weeks postoperatively. Passive motion exercises were permitted starting at 4 weeks postoperatively, and active range of motion exercises were permitted at 6 weeks postoperatively. At the patient’s most recent follow-up 30 months after surgery, the patient reported no restriction of the activities of daily living. Radiographs revealed no lucent line on the humerus and glenoid components, although bone resorption and superior retraction of the tuberosities on both sides were observed. Conclusions. Single-stage bilateral RSA improved shoulder function, but healing of the greater tuberosity can affect the improvement in external rotation after the operation. Although a long-term follow-up is needed, single-stage bilateral RSA appears to be a viable treatment option.